2020
DOI: 10.1002/cad.20336
|View full text |Cite
|
Sign up to set email alerts
|

Getting the Baby on a Schedule: Dutch and American Mothers’ Ethnotheories and the Establishment of Diurnal Rhythms in Early Infancy

Abstract: One of the earliest challenges for infants and their parents is developing a diurnal sleep–wake cycle. Although the human biological rhythm is circadian by nature, its development varies across cultures, based in part on “zeitgebers” (German: literally “time‐givers”) or environmental cues. This study uses the developmental niche framework by Super and Harkness to address two different approaches to getting the baby on a schedule. 33 Dutch and 41 U.S. mothers were interviewed when their babies were 2 and 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Five studies were conducted in the United States (Ajao et al, 2011; Chianese et al, 2009; Joyner et al, 2010; Oden et al, 2010; Stiffler et al, 2020), and one each in the United Kingdom (Rudzik & Ball, 2016), Taiwan (Tsai et al, 2014), Vietnam (Murray et al, 2019) and Norway (Sviggum et al, 2018). One study included participants from both the USA and the Netherlands (van Schaik et al, 2020). Sample sizes vary from 5 (Sviggum et al, 2018) to 83 (Ajao et al, 2011; Joyner et al, 2010; Oden et al, 2010), with the majority ( n = 8) of parents having infants younger than 6 months of age.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies were conducted in the United States (Ajao et al, 2011; Chianese et al, 2009; Joyner et al, 2010; Oden et al, 2010; Stiffler et al, 2020), and one each in the United Kingdom (Rudzik & Ball, 2016), Taiwan (Tsai et al, 2014), Vietnam (Murray et al, 2019) and Norway (Sviggum et al, 2018). One study included participants from both the USA and the Netherlands (van Schaik et al, 2020). Sample sizes vary from 5 (Sviggum et al, 2018) to 83 (Ajao et al, 2011; Joyner et al, 2010; Oden et al, 2010), with the majority ( n = 8) of parents having infants younger than 6 months of age.…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes vary from 5 (Sviggum et al, 2018) to 83 (Ajao et al, 2011; Joyner et al, 2010; Oden et al, 2010), with the majority ( n = 8) of parents having infants younger than 6 months of age. Qualitative data was collected via a variety of methods, including focus groups (Chianese et al, 2009; Rudzik & Ball, 2016; Stiffler et al, 2020), interviews (Sviggum et al, 2018; Tsai et al, 2014; van Schaik et al, 2020), a combination of focus groups and interviews (Ajao et al, 2011; Joyner et al, 2010; Oden et al, 2010) and photo elicitation (Murray et al, 2019). The aims of these studies fell into one of two categories: investigating factors that influence parental decisions (Ajao et al, 2011; Chianese et al, 2009; Joyner et al, 2010; Oden et al, 2010; Stiffler et al, 2020) and exploring parents' experiences with infant sleep (Murray et al, 2019; Rudzik & Ball, 2016; Sviggum et al, 2018; Tsai et al, 2014; van Schaik et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…63 Cross-cultural evidence revealed that, in the Netherlands, beliefs on rest and regularity prevail above beliefs about the stimulation of motor development among parents. 65,66 As a growing body of evidence points out that Dutch infants seem to develop at a slower pace than in other Western societies, 27,28,41 parental beliefs on motor development are an important factor to consider when studying the progress of infants in their gross motor development.…”
Section: Parental Beliefs On Motor Developmentmentioning
confidence: 99%